Switching Safely: Pharmacokinetics, Efficacy and Safety of Switching Efavirenz to Maraviroc Twice Daily in Patients on Suppressive Antiretroviral Therapy. Issue 2 (February 2015) - Waters, Laura; Jackson, Akil; Else, Laura; Rockwood, Neesha; Newell, Sally; Back, David; Nelson, Mark; Gazzard, Brian; Boffito, Marta
Background: CYP3A4 induction by efavirenz (EFV) persists after drug cessation; we assessed the pharmacokinetics (PK), efficacy and safety of maraviroc (MVC) administered to HIV-infected individuals switching from EFV-containing therapy. Methods: Patients with R5-tropic virus and suppressed viral load on two nucleoside/nucleotide reverse transcriptase inhibitors (NRTIs) plus EFV switched EFV to MVC 600 mg twice daily for 14 days, and then to MVC 300 mg twice daily. Following screening, three intensive PK visits were performed (sampling was pre-dose and 1, 2, 4, 6, 8 and 12 h post-dose): day 1 (VISIT 1, MVC 600 mg twice daily), day 14 (VISIT 2, steady-state MVC 600 mg twice daily) and day 28 post regimen switch (VISIT 3, steady-state MVC 300 mg twice daily); MVC trough concentration (Ctrough ) was determined 3, 6 and 10 days following regimen switch and viral loads up to week 24. MVC PK parameters on visits 1 and 2 and MVC Ctrough on day 6 were compared to visit 3 (reference) via geometric mean ratios (GMR) and 95% CIs. Results: Twelve males completed the study. MVC PK parameters at visit 1 versus visit 3 were: GMR and 95% CI 12-h area under the curve (AUC0–12 ) 1.25 (1.00, 1.58); Cmax 1.64 (1.16, 2.31); Ctrough 0.61 (0.46, 0.80). Visit 2 MVC PK parameters were significantly higher than visit 3: GMR and 95% CI AUC0–12 2.31 (1.84, 2.90); Cmax 2.42 (1.87, 3.12); Ctrough 2.25 (1.74, 2.91). MVC was well tolerated with no grade 3/4 adverse events; all subjects maintained viral suppression to the end of the study. Conclusions: The EFV induction effect necessitated increased MVC dose to 600 mg twice daily following switch and persisted for approximately one week after EFV cessation. This is less than the 2-week induction observed when switching EFV to etravirine and highlights the importance of studying different tail interactions. Higher dose MVC was well tolerated. All measured MVC Ctrough concentrations exceeded wild-type 90% inhibitory concentration.